A Review on Structural Configurations of Magnetorheological Fluid Based Devices Reported in 2018–2020 - Hua, Dezheng; Liu, Xinhua; Li, Zengqiang; Fracz, Pawel; Hnydiuk-Stefan, Anna; Li, Zhixiong (Frontiers in Materials, 2021)
Magnetorheological (MR) ﬂuid is a kind of smart materials with rheological behavior change by means of external magnetic ﬁeld application, which has been widely adopted in many complex systems of different technical fields. In this work, the state-of-the-art MR ﬂuid-based devices are reviewed according to structural configurations reported from 2018 to 2020. Based on the rheological characteristic, MR fluid has a variety of operational modes, such as ﬂow mode, shear mode, squeeze mode and pinch mode, and plays unique advantages in some special practical applications. Thus, referring to these operational modes, improved engineering mechanical devices with MR fluid are summarized including brakes, clutch, damper and mount proposed over the last three years. Furthermore, some new medical devices used MR fluid are also investigated, for instance, surgical assistive devices and artificial limb. In particular, some outstanding advances on structural innovations and application superiority of these devices are introduced in detail. Finally, an overview of the significant issues occurred in the MR fluid-based devices is reported, and the developing trends are discussed for the devices with MR fluid.